Development and characterization of human single chain antibody against Iranian Macrovipera lebetina snake venom. (15th July 2021) - Eskafi, Ayda Hassanzadeh; Bagheri, Kamran Pooshang; Behdani, Mahdi; Yamabhai, Montarop; Shahbazzadeh, Delavar; Kazemi-Lomedasht, Fatemeh
Abstract: Snakebite is an important public health problem in tropical and subtropical regions. Macrovipera lebetina is one of the most dangerous snakes in Iran. Envenoming by this snake can lead to respiratory distress, heart attack, bleeding, and death. The specific treatment available is immunized equine serum, which has several side effects like serum sickness. Nowadays, single-chain fragment variable antibodies (scFvs) are one of the fast growing classes of monoclonal antibodies, which are suggested for treatment of envenoming. This study aimed to achieve a fully human scFv antibody against M. lebetina venom from human non-immune library. In this study, scFvs against M. lebetina venom were isolated by phage display technique. Using three rounds of biopanning, two specific scFvs (C37 and C69) with the highest affinity were selected. The selected scFvs purified by nickel affinity chromatography. The specific binding of purified antibodies were confirmed by enzyme-linked immunosorbent assay. The LD50 as well as HD50 concentration of the crude venom were obtained to be 45 μg and 120 μg/ml, respectively. C69 neutralized 48% of the hemolysis activity of M. lebetina venom and C37 survived 66% of mice after 115 min of envenoming. Taken together, the results indicate the potential of human non-immune libraries for selection of functional antibodies against M. lebetina venom. Graphical abstract: Image 1 Highlights: Single chain antibodies against Macrovipera lebetina venom were isolated from human non-immune antibody library. Two specific single-chain variable fragment antibodies with the highest affinity were selected. The results indicate for potential of selected antibodies against Macrovipera lebetina venom.